Methods of Palaeodemography: The Case of the Iberian Oppida and Roman Cities in North‐East Spain. Issue 3 (23rd July 2019) - Sinner, Alejandro G.; Carreras, Cesar
Summary: Ancient demography is a recurrent topic in archaeology, thanks to new methods and evidence from different surveys and excavations. However, different cultures or periods are studied on their own, without any comparison being made between them and of their population dynamics. The present paper seeks to advance the situation by defining methodologies to allow diachronic comparisons between two different periods and cultures. After setting out a methodological approach, the paper goes on to apply the same to a case study: namely the Roman conquest of north‐east Spain, comparing the demography of the ancient Iberian communities (fourth‐second centuries BCE) to the Roman colonization (first century BCE to first century CE). Roman urbanism is generally supposed to increase the population in a particular territory, but our present evidence refutes this point: a decrease in population is visible in urban or proto‐urban sites from the Iberian to Roman periods, though there is an increase in the rural densities.